2018
DOI: 10.3390/v10080405
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Immunity and the Natural History of Congenital Human Cytomegalovirus Infection

Abstract: Congenital human cytomegalovirus (HCMV) is the most common viral infection of the developing fetus, and a significant cause of neurodevelopmental abnormalities in infants and children. Congenital HCMV infections account for an estimated 25% of all cases of hearing loss in the US. It has long been argued that maternal adaptive immune responses to HCMV can modify both the likelihood of intrauterine transmission of HCMV, and the severity of fetal infection and risk of long term sequelae in infected infants. Over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 115 publications
2
105
0
Order By: Relevance
“…These results demonstrated that postnatal infection of CMV in infants with gestational age ≥ 32 weeks does not cause obvious adverse influence on the health of infants. The minimal influence on the health of infants may be associated with the presence of maternal CMV IgG in infants, which can neutralize the virulence of CMV and provide substantial protection against symptomatic diseases or sequelae [21].…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that postnatal infection of CMV in infants with gestational age ≥ 32 weeks does not cause obvious adverse influence on the health of infants. The minimal influence on the health of infants may be associated with the presence of maternal CMV IgG in infants, which can neutralize the virulence of CMV and provide substantial protection against symptomatic diseases or sequelae [21].…”
Section: Discussionmentioning
confidence: 99%
“…As many as 1% of newborns are infected with congenitallyacquired HCMV infections that can cause life-long neurological problems including microcephaly, mental defects, and hearing loss (Britt, 2018;Permar et al, 2018). The virus can infect neural progenitor cells where pp71 expression results in slight decreases in the steady state levels of JAG1 and NICD1, components of the Notch pathway (Li et al, 2015).…”
Section: Pathogenesismentioning
confidence: 99%
“…Even though HCMV infection is asymptomatic in immunocompetent individuals, it may lead to several lifethreatening conditions in immunosuppressed subjects, such as organ and stem cell transplant recipients or AIDS patients. Furthermore, it can cause severe morbidity in congenitally infected children and elderly people (Cannon et al, 2010;Manicklal et al, 2013;Tu and Rao, 2016;Britt, 2018). Additionally, spontaneous reactivation of latent endogenous virus and/or superinfection with multiple viral strains can contribute to the overall burden and individual disease severity, as neither a vaccine nor an effective cure is currently available (Schleiss et al, 2017).…”
Section: Introductionmentioning
confidence: 99%